The Effects of Coding Literacy and Computational Thinking on Student Digital Entrepreneurial Intentions: The Mediating Role of Coding Self-Efficacy - Saputra, Hadi Kurnia; Ganefri, Ganefri; Yulastri, Asmar; Yuliana, Yuliana (Voteteknika (Vocational Teknik Elektronika dan Informatika), 2025)
Digital transformation has intensified the importance of digital entrepreneurship as a strategic pathway for university students. This study examines the effects of Coding Literacy and computational thinking on student Digital Entrepreneurial intentions, with coding self-efficacy serving as a mediating variable. A quantitative explanatory design was employed using survey data collected from 119 undergraduate students enrolled in an introductory coding course at Universitas Negeri Padang. Data were analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM). The results indicate that Coding Literacy significantly influences coding self-efficacy (β = 0.414, p < 0.001) and Digital Entrepreneurial intentions (β = 0.474, p < 0.001). Computational thinking also shows a significant positive effect on coding self-efficacy (β = 0.340, p = 0.002), but does not exert a significant direct effect on Digital Entrepreneurial intentions (β = 0.074, p = 0.395). Furthermore, coding self-efficacy has a strong positive effect on Digital Entrepreneurial intentions (β = 0.313, p < 0.001). Mediation analysis reveals that coding self-efficacy partially mediates the relationship between Coding Literacy and Digital Entrepreneurial intentions (β = 0.130, p = 0.002), while fully mediating the relationship between computational thinking and Digital Entrepreneurial intentions (β = 0.107, p = 0.035). The model explains 49.3% of the variance in coding self-efficacy and 60.7% of the variance in Digital Entrepreneurial intentions. These findings highlight coding self-efficacy as a critical psychological mechanism that transforms computational competencies into Digital Entrepreneurial intentions, offering important implications for the design of coding-oriented entrepreneurship education in higher education.Keywords— Coding Literacy, computational thinking, coding self-efficacy, digital entrepreneurial intention, PLS-SEM